Penggunaan Teknologi Informasi Untuk Meningkatkan Produktifitas Kerja Karyawan (Studi Kasus pada PT. Aksara Solopos Surakarta) - Alfianita Maharani, Ayu, Ahmad Mardalis, SE., MBA (2017)
ABSTRACT The purpose of this study are: 1) To determine the level of productivity of employees at PT. Aksara Solopos Surakarta; 2) To determine the use of information technology at PT. Aksara Solopos Surakarta; 3) To determine the effect of the use of information technology on productivity of employees at PT. Aksara Solopos Surakarta.This study uses primary data. The sample in this study were 67 respondents. The sampling technique using a simple random sampling or random sampling. The analytical method used is to test the validity, reliability test and multiple linear regression analysis with the first performed classical assumption that include normality test, multicolinearity and heterokedastisitas test. By hypothesis testing using significance together (Test-F) and partial significance test (t-test) and the coefficient of determination (R2).Results: 1) The level of productivity of employees at PT. Aksara Solopos Surakarta quite good because of the use of information technology that make the job more effectively and efficiently. 2) The use of information technology at PT. Aksara Solopos Surakarta quite good because of the use of information technology to support the needs of employees. 3) The use of information technology and significant positive effect on the productivity of employees at PT. Aksara Solopos Surakarta. Keywords: Expertise use of information technology, the intensity of the use of information technology, and employee productivity.